(untitled) (Моделювання, керування та інформаційні технології, 2025)
This paper presents a structured threat evaluation framework for environmental security in military contexts, focusing on radiological and chemical hazards. It introduces a threat taxonomy that links specific sources such as reactor accidents, radiological dispersal devices, and toxic industrial chemicals to operational settings and exposure pathways. A probability–severity risk model is proposed, allowing for threshold-based decision-making aligned with established safety standards. Monitoring requirements and performance indicators including alarm delay, source localization accuracy, and forecast error are defined to ensure timely and effective response. Scenario analyses demonstrate the framework’s ability to reduce decision latency, improve resource allocation, and enhance operational protection for personnel and infrastructure. The proposed model supports continuous system refinement through measurable targets, structured feedback, and integration with command decision systems.